PERBEDAAN PENGETAHUAN SIKAP DAN PERILAKU PENDERITA KELUARGA DAN MASYARAKAT TERHADAP EPILEPSI - Suryani Gunadharma,* Paranita Utama,* Sobaryati,* Ahmad Rizal,* Lisda Amalia,* Uni Gamayani* (NEURONA, 2020)
INTRODUCTION ACHIEVEMENT OF EPILEPSY TREATMENT DEPENDS ON THE UNDERSTANDING OF PATIENTS ABOUT THEIR DISEASE COMPLIANCE OF ANTIEPILEPTIC DRUGSFAMILY AND COMMUNITIES SUPPORT GENDER AGE LEVEL OF EDUCATION SOCIOCULTURAL ECONOMIC STATUSAND ENVIRONMENT AFFECT EPILEPSY PERCEPTIONT